A Rare Cause of Upper Airway Obstruction in a Child - H. Ahmed; C. Ndiaye; M. W. Barry; Aliou Thiongane; A. Mbaye; Y. Zemene; I. C. Ndiaye (Case Reports in Otolaryngology)
Ventricular band cyst is a rare condition in children but can result in severe upper airway obstruction with laryngeal dyspnea or death. The diagnosis should be considered in any stridor in children with previous history of intubation or respiratory infections. We report a case of a 4-year-old girl, received in an array of severe respiratory distress, emergency endoscopy was done, and a large ventricular tape band cyst obstructing the air way was found. Complete excision was made, and postoperative prophylaxis tracheotomy was done. The postoperative course was uneventful with improvement of clinical and endoscopic signs.